2004
DOI: 10.1524/ract.92.12.855.55112
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the formation of sodium hassate(VIII)

Abstract: Element 108 / Hassium / Volatile HsO 4 / In-situ production / Adsorption on hydroxide / CALLISTO Summary. Hassium, element 108, was produced in the fusion reaction between 26 Mg and 248 Cm. The hassium recoils were oxidized in-situ to a highly volatile oxide, presumably HsO 4 , and were transported in a mixture of He and O 2 to a deposition and detection system. The latter consisted of 16 silicon PIN-photodiodes facing a layer of NaOH, which served, in the presence of a certain partial pressure of water in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 18 publications
2
26
0
4
Order By: Relevance
“…This gas mixture transported HsO 4 and simultaneously produced OsO 4 to a linear array of 12 detectors (PIN-diodes) facing a stainless steel plate coated with a thin film of NaOH. From the adsorption pattern of HsO 4 and OsO 4 at the beginning of the chemically reactive NaOH surface, presumably forming Na 2 [HsO 4 (OH) 2 ] in analogy to the know osmate (VIII), it was concluded that HsO 4 and OsO 4 show a similar reactivity in this first acid-base reaction with HsO 4 [155]. This is in agreement with a theoretical calculation [230].…”
Section: Hassium (Hs Element 108)supporting
confidence: 85%
See 3 more Smart Citations
“…This gas mixture transported HsO 4 and simultaneously produced OsO 4 to a linear array of 12 detectors (PIN-diodes) facing a stainless steel plate coated with a thin film of NaOH. From the adsorption pattern of HsO 4 and OsO 4 at the beginning of the chemically reactive NaOH surface, presumably forming Na 2 [HsO 4 (OH) 2 ] in analogy to the know osmate (VIII), it was concluded that HsO 4 and OsO 4 show a similar reactivity in this first acid-base reaction with HsO 4 [155]. This is in agreement with a theoretical calculation [230].…”
Section: Hassium (Hs Element 108)supporting
confidence: 85%
“…Over the last decades, in addition to the above mentioned techniques and devices, several very unique detection systems for highly volatile or gaseous products were developed; among them a cryo-detector [154] for the search for SHE, CALLISTO [155] for a study of HsO 4 interacting from the gas phase with solid sodium hydroxide, OSCAR [156] for a search for 272 Hs, and a combination of ionization chamber and neutron-multiplicity detector in an experiment to search for element 112 [157].…”
Section: Techniques and Instruments For Gas-phase Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Following the example of Zhuikov [141], several groups have adopted the in-situ production of volatile tetroxides directly behind the target by adding oxygen (typically 10%) to the carrier gas that contains no aerosol particles [142][143][144]. Typically, the reaction products were transported with the carrier gas through a quartz column containing a quartz wool plug heated to some 600…”
Section: Resultsmentioning
confidence: 99%